2013
DOI: 10.2337/db12-1093
|View full text |Cite
|
Sign up to set email alerts
|

TCF7L2 Variation and Proliferative Diabetic Retinopathy

Abstract: Proliferative diabetic retinopathy (PDR) is the most severe vision-threatening complication of diabetes. For investigation of genetic association between TCF7L2 and PDR in Caucasian type 2 diabetes mellitus (T2DM) and its functional consequences, 383 T2DM patients with PDR (T2DM-PDR) and 756 T2DM patients without diabetic retinopathy (T2DM–no DR) were genotyped with rs7903146 in TCF7L2. We found that risk allele (T) frequency of rs7903146 was significantly higher in T2DM-PDR patients (allelic P = 2.52E-04). In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 27 publications
0
42
0
Order By: Relevance
“…An association with PDR in Caucasians with T2D and replication in an independent cohort was reported [33]. This study had a reasonable sample size (n = 1,139 in the discovery and replication cohorts combined), used the PDR phenotype, and defined controls stringently with a minimum diabetes duration of 15 years.…”
Section: Candidate Gene Association Studiesmentioning
confidence: 98%
See 1 more Smart Citation
“…An association with PDR in Caucasians with T2D and replication in an independent cohort was reported [33]. This study had a reasonable sample size (n = 1,139 in the discovery and replication cohorts combined), used the PDR phenotype, and defined controls stringently with a minimum diabetes duration of 15 years.…”
Section: Candidate Gene Association Studiesmentioning
confidence: 98%
“…This study had a reasonable sample size (n = 1,139 in the discovery and replication cohorts combined), used the PDR phenotype, and defined controls stringently with a minimum diabetes duration of 15 years. TCF7L2 had already been studied in DR with both positive [33,34] and negative results [32,35]. Further investigation in other T2D populations is warranted.…”
Section: Candidate Gene Association Studiesmentioning
confidence: 99%
“…For instance, variants in the TCF7L2 gene were found to promote pathological retinal neovascularization via ER stress-dependent upregulation of VEGFA 34 . Moreover, the receptor for advanced glycation end-product ( RAGE ) gene polymorphism -2245G/A was shown to upregulate expression of NF-κB p65 , plasma MCP-1 , AOPP and pentosidine, all of which are pro-inflammatory, oxidative-glycation markers 35 .…”
Section: Diabetic Retinopathy (Dr)mentioning
confidence: 99%
“…9 Among these genetic variants, rs7903146 on the chromosome 10q25 region has been the most frequently reported to be strongly associated with T2DM. 8,[10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] It was also reported that TCF7L2 gene rs7903146 is linked with microvascular and macrovascular complications, such as coronary artery disease, 30,31 nephropathy, 20,32,33 retinopathy, 32,[34][35][36][37][38][39][40] and neuropathy. 37 However, some studies demonstrated that TCF7L2 rs7903146 is not consistently associated with DR, 32,34,35,38,39 while others suggested TCF7L2 genetic variability contributes to the development of DR. 36,37,40 Clarification of the actual role of TCF7L2 rs7903146 in DR process and identification of its function as a genetic risk marker will assist ophthalmologists to predict and debilitate diabetes complication.…”
Section: Introductionmentioning
confidence: 99%
“…All studies were case-control studies, of which two studies were performed on East Asian and six on Caucasian. Three studies had larger sample sizes, 36,38,39 the total cases were 1139, 1129 and 1206, respectively. Other five studies had relatively small sizes (numbers of cases < 1000).…”
Section: Characteristics Of the Available Studiesmentioning
confidence: 99%